Victim Blaming sebagai Bentuk Reviktimisasi Sekunder dalam Perspektif Viktimologi di Indonesia - Indah Sari Br Barus; Nia Utami Ritonga (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study examines the phenomenon of victim blaming as a form of secondary victimization within the perspective of victimology in Indonesia. Victim blaming remains a significant issue where victims of crime, particularly in cases of violence, are often blamed for the incidents they experience. This condition not only exacerbates the psychological and social suffering of victims but also hinders their access to justice. The objective of this research is to analyze how victim blaming occurs and to understand its impact as a form of secondary victimization. This study employs a normative juridical method with a qualitative approach, using literature review from legal documents, journals, and relevant academic sources. The findings indicate that victim blaming is influenced by social stigma, cultural perspectives, and a lack of public awareness regarding victims’ rights. Furthermore, such practices result in secondary victimization, where victims experience repeated harm due to negative societal responses. From a victimological perspective, victim blaming contradicts the principle of victim protection and justice. The implication of this research highlights the need for stronger legal protection, public education, and a more victim-centered approach in addressing crime in Indonesia.